Genotypes and phenotypes of neurofibromatosis type 1 patients in Japan: A Hereditary Tumor Cohort Study - Mashu Futagawa; Tetsuya Okazaki; Eiji Nakata; Chika Fukano; Risa Osumi; Fumino Kato; Yusaku Urakawa; Hideki Yamamoto; Toshifumi Ozaki; Akira Hirasawa (Human Genome Variation)
Abstract Neurofibromatosis type 1 (NF1) presents with a broad spectrum of clinical manifestations, including an increased risk of tumor development and hypertension. Comprehensive data on genotype‒phenotype correlations in patients with NF1 are limited. Therefore, in this study, we aimed to elucidate the detailed genetic and clinical characteristics of NF1 in a hereditary tumor cohort. We performed sequencing and copy number assays in a clinical laboratory and analyzed the clinical data of 44 patients with suspected NF1. Germline pathogenic variants were detected in 36 patients (81.8%), and 20.7% of the variants were novel. Notably, 40.0% of adult patients presented with malignancies; female breast cancer occurred in 20.0% of patients, which was a higher rate than that previously reported. Hypertension was observed in 30.6% of the adult patients, with one patient experiencing sudden death and another developing pheochromocytoma. Three patients with large deletions in NF1 exhibited prominent cutaneous, skeletal, and neurological manifestations. These results highlight the importance of regular surveillance, particularly for patients with malignancies and hypertension. Our findings provide valuable insights for genetic counseling and clinical management, highlighting the multiple health risks associated with NF1 and the need for comprehensive and multidisciplinary care.